2011
DOI: 10.1039/c0cc04734a
|View full text |Cite
|
Sign up to set email alerts
|

Contra-diffusion synthesis of ZIF-8 films on a polymer substrate

Abstract: ZIF-8 films were successfully prepared on a flexible nylon substrate with a contra-diffusion synthesis method, and gas permeation experiments indicated that the films were continuous and compact.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
249
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 333 publications
(253 citation statements)
references
References 26 publications
2
249
1
1
Order By: Relevance
“…21 Wang and colleagues synthesized a highly permeable ZIF-8 membrane on a exible nylon polymer using a contra-diffusion synthetic method. 22 However, the H 2 -N 2 selectivity of the ZIF-8 membrane was only 3.7, indicating that macroporous defects were present in the membrane layer. In the present work, attributed to the formation of strong non-covalent and covalent bonds between the SSN and the ZIF-8 membrane layer, 36 the ZIF-8 membranes were attracted and anchored onto the support surface for the facile synthesis of well-intergrown ZIF-8 membranes, which is helpful for reducing the defect density and thus enhancing the separation selectivity.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…21 Wang and colleagues synthesized a highly permeable ZIF-8 membrane on a exible nylon polymer using a contra-diffusion synthetic method. 22 However, the H 2 -N 2 selectivity of the ZIF-8 membrane was only 3.7, indicating that macroporous defects were present in the membrane layer. In the present work, attributed to the formation of strong non-covalent and covalent bonds between the SSN and the ZIF-8 membrane layer, 36 the ZIF-8 membranes were attracted and anchored onto the support surface for the facile synthesis of well-intergrown ZIF-8 membranes, which is helpful for reducing the defect density and thus enhancing the separation selectivity.…”
Section: Resultsmentioning
confidence: 99%
“…In the last ve years, more and more effort has been paid to the preparation of ZIF-8 membranes by in situ growth, secondary growth, and also the liquid phase epitaxy method. [16][17][18][19][20][21][22][23][24][25]33 However, it was oen found that separate ZIF-8 crystals or islands rather than continuous layers were formed on the native ceramic supports by direct solvothermal synthetic routes because heterogeneous nucleation of ZIF-8 crystals on the support surfaces was very poor. 17,26 Therefore, seed coating 20,21 or chemical modication 17,26 of the supports have been applied to promote the heterogeneous nucleation of ZIF-8 crystals on support surfaces.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…302,303 If a porous support is used for the separation of an aqueous and an organic solvent, one of the solvents contains the metal ion and the other contains the linker molecule. A MOF layer forms at the contact zone of the polymer support-aqueous solvent 304,305 or inorganic support-organic solvent. 306 Recently, a concept for a scalable and inexpensive processing of MOF membranes in polymeric hollow fibers has been developed.…”
mentioning
confidence: 99%
“…Literatürde bu iki yöntemden farklı olarak yeni bir yöntem olan kontra-difüzyon yöntemi (contra-diffusion) veya arayüzeyde sentez (interfacial synthesis) olarak da adlandırılan yöntemle difüzyon hücre sisteminin kullanımıyla çeşitli membranlar sentezlenebilmektedir [22]. Çok yaygın olmayan bu yöntemle genellikle polimer destek üzerinde MOF membranlar sentezlenmiştir [23][24][25][26]. Seramik desteklerin kullanıldığı çalışmalar birkaç adetle sınırlıdır [27,28].…”
Section: Introductionunclassified